Paint and coating containing single ion conductor polymer and lithium ion battery
By using a single-ion conductor polymer coating on the negative electrode interface of the lithium-ion battery, a stable solvated structure is constructed, which solves the problems of uneven lithium deposition and instability of the SEI interface in the lithium-ion battery, and significantly improves the cycling stability and safety of the battery.
Patent Information
- Application Number
- CN202510023564.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
When using metal lithium lithium, the solid electrolyte interface is unstable, resulting in uneven lithium deposition and frequent side reactions, affecting electrochemical performance and safety.
Using coatings and coatings containing single ion conductor polymers, the stability of the SEI interface is improved by constructing a stable solvation structure on the negative electrode interface, adjusting the lithium ion flux and inhibiting the growth of lithium dendrites.
It effectively reduces the consumption and side reaction of active lithium required for the formation of SEI film, promotes uniform nucleation of lithium at the interface and lateral diffusion and deposition of ion nanochannels along the interface, and improves the cycling stability and safety of the battery.
Smart Images

Figure CN119812340A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a paint and coating containing a single ion conductor polymer and a lithium ion battery. Background Art
[0002] Over the past few decades, lithium-ion batteries (LiBs) have revolutionized energy storage systems and have become indispensable. With high energy density and stable cycling, lithium-ion batteries have gradually replaced traditional energy storage devices such as nickel-cadmium (Ni-Cd), nickel-metal hydride (Ni-MH), and lead-acid batteries. Lithium batteries have recently been widely used in portable electric devices, electric vehicles, and grid-scale energy storage. The energy density of current lithium battery systems based on transition metal oxide lithium cathodes, graphite anodes, and carbonate-based electrolytes is about 800Wh·L –1 However, intercalation-based lithium battery chemistries have intrinsic capacity limitations, and the increasing demand for higher energy storage systems has driven the development of new battery chemistries.
[0003] There are many challenges in using metallic lithium in commercial battery systems. One of the fundamental sources of these challenges is the solid electrolyte interface (SEI) between metallic lithium and the electrolyte. Since the deposition and stripping reactions of lithium are mainly governed by the interfacial properties, a stable and uniform interface is essential for good electrochemical properties such as high Coulombic efficiency, low resistance, and stable cycling performance. When the interface is unstable and non-uniform, the non-uniformity of lithium deposition and parasitic side reactions are accelerated, leading to critical safety issues as well as poor electrochemical performance. The differences in the interface inevitably affect interfacial phenomena such as the wettability of the electrolyte to metallic lithium, the Li + Ion transfer and SEI formation cause different interface problems.
[0004] Generally speaking, the SEI layer consists of ROCO 2 Li, ROLi, Li 2 CO 3 and LiF, which can be changed by the electrolyte composition. Inorganic substances such as Li 2 CO 3 , Li 2 O and LiF are mainly in the inner layer, while the outer layer of SEI is mainly composed of organic matter, including ROOLi, ROCO 2 Li and RCOO 2 Li. SEI has the properties of electrical insulation and ion conductivity, preventing direct contact between the electrolyte and metallic lithium, but allowing Li + Ions migrate through the SEI layer. Ideally, the SEI layer will prevent continuous electrolyte decomposition on the surface of metallic lithium and provide Li +The uniform distribution of ion flow leads to uniform lithium deposition. However, the actual SEI layer is uneven, sparse and porous, and cannot prevent direct contact between the electrolyte and metallic lithium. In addition, the composition of the SEI layer is not strong enough to adapt to the huge volume changes of metallic lithium during lithium deposition and stripping. Therefore, the volume expansion of the SEI layer during deposition and the volume contraction during stripping are easily punctured, resulting in severe cracks in the SEI layer. Since the interfacial resistance of the newly exposed Li surface at the crack is much lower than that of the Li surface covered by the complete SEI, Li + Ions are preferentially deposited at these cracks. As a result, metallic lithium protrusions grow non-uniformly from the cracks, resulting in heterogeneous lithium deposition. In addition, the newly deposited metallic lithium inevitably produces a new lithium surface. Due to the high reactivity of the fresh lithium surface, the electrolyte decomposes on the surface, forming a new SEI layer on the newly deposited lithium surface. The repeated destruction and remodeling of the SEI layer resulting from uneven lithium deposition and stripping brings about a continuous consumption of electrolyte and metallic lithium, resulting in increased interfacial resistance and low Coulombic efficiency. Therefore, constructing a strong and stable SEI formation is crucial to solving these problems.
[0005] Currently, the research on stable SEI reported publicly is mostly to construct an electrolyte and a metal lithium negative electrode derived SEI by optimizing the solvation structure of the electrolyte including solvents, lithium salts and film-forming additives. For example, CN201310085382.8 discloses a lithium-ion secondary battery electrolyte comprising a solvent, a lithium salt and a film-forming additive, and obtains a solvent system with a high dielectric constant and low viscosity by linear carboxylic acid esters and ethylene carbonate, and optimizes the electrode compatibility by using film-forming additives, thereby achieving an improvement in battery cycle performance. However, the electrolyte-derived SEI is bound to consume a large amount of lithium salts and solvents during the cycle, which is not conducive to the long cycle stability of the battery. For example, CN201911382604.6 discloses a method of forming an inner layer by alloying metal with lithium, and coating a polymer layer mixed with lithium salts on the outside to achieve the construction of a negative electrode stable interface. However, the process conditions are harsh and the process is cumbersome, which limits the quantification in actual production.
[0006] Moreover, single-ion conductive polymers are currently mainly used as polymer solid electrolytes. Lithium ions are difficult to dissociate, and the ionic conductivity (σ) is generally low at room temperature (10 -7 ~10 -5 S cm -1) has affected its practical application. In addition, conventional single-ion conductor polymers mainly adopt the double-bond free radical polymerization mechanism under light initiation or initiation conditions, and the anion site dispersion is very uneven; and the method of chemically modifying the surface of the polymer after film formation to construct single-ion conductor polymers has the problem of incomplete chemical reaction substitution and uneven distribution of anion sites. In particular, single-ion conductor polymers generally have a more complicated synthesis process, and the use of polymer solid electrolytes obviously has a high preparation cost, and unlimited reduction of their use in batteries is bound to significantly reduce their costs and is conducive to the further advancement of industrialization. Therefore, it is necessary to provide a new single-ion conductor polymer to improve the above problems. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a coating and a lithium ion battery comprising a single ion conductor polymer. The coating can actively adjust the micro-sized solvation structure at the negative electrode interface, can participate in the construction of a stable SEI interface, and is easy to prepare, and has a better prospect for industrial production.
[0008] To achieve the above object, the present invention provides a coating, which comprises a single ion conductor polymer having a structure shown in formula (I) and a polar organic solvent;
[0009]
[0010] n is 5 to 1000;
[0011] Z means N, B or P;
[0012] R 1 express Wherein, m is 2 to 100; X represents a Group VI A element; Y 1 , Y 2 , Y 3 , Y 4 Each independently represents H or halogen; R 11 and R 12 Each independently represents a substituted or unsubstituted C1-C10 alkylene group, and the substitution position is a carbon atom and / or a hydrogen atom on the C1-C10 alkylene group; when the substitution position is a carbon atom on the C1-C10 alkylene group, the substituent is -O- or -S-; when the substitution position is a hydrogen atom on the C1-C10 alkylene group, the substituent is -F, -CH 3 or = O; R 2 and R 3 Each is independently selected from one or a combination of two or more of F-substituted or unsubstituted C1-C4 alkylene, phenylene ring, naphthalene ring or heterocyclic ring, and the heteroatom in the heterocyclic ring is selected from N, O or S.
[0013] Further, n is 20 to 200;
[0014] R 1 for wherein m is 2 to 50; X is selected from O and / or S; R 11 Selected from -(CH 2 ) a -、-(CF 2 ) a -、-(CHF) a -、-CH 2 CH(CH 3 )C(O)-、-CH 2 CH 2 C(O)-、-S(CH 2 ) a -、-S(CF 2 ) a -、-S(CHF) a -、-SCH 2 CH(CH 3 )C(O)-、-SCH 2 CH 2 C(O)-、-O(CH 2 ) a -、-O(CF 2 ) a -、-O(CHF) a -and-OCH 2 CH(CH 3 )C(O)- or a combination of two or more thereof, a is 1 to 10; R 12 Selected from -(CH 2 ) b -、-(CF 2 ) b -、-(CHF) b -、-OC(O)CH 2 CH(CH 3 )-、-OC(O)CH 2 CH 2 -、-S(CH 2 ) b -、-(CF 2 ) b S-、-(CHF) b S-、-OC(O)CH(CH 3 )CH 2 S-、-OC(O)CH 2 CH 2 S-、-(CH 2 ) b O-、-(CF 2 )b O-、-(CHF) b O- and -OCH 2 CH(CH 3 )C(O)O- or a combination of two or more thereof, b is 1 to 10; Y 1 , Y 2 , Y 3 , Y 4 Each independently represents H or F;
[0015] R 2 and R 3 Each is independently selected from one or a combination of two or more of F-substituted or unsubstituted C1-C4 alkylene, a phenylene ring, a naphthalene ring, a sub-five-membered heterocyclic ring or a sub-six-membered heterocyclic ring, and the heteroatoms in the sub-five-membered heterocyclic ring and the sub-six-membered heterocyclic ring are independently selected from N, O or S.
[0016] Further, the number average molecular weight of the single ion conductor polymer is 10000 to 20000 g / mol;
[0017] Z stands for N;
[0018] R 1 for Wherein, m is 2 to 7; X represents O and / or S; R 11 Selected from -(CH 2 ) a -、-SCH 2 CH 2 C(O)-, a is 1 to 4; R 12 Selected from -S(CH 2 ) b -、-OC(O)CH 2 CH 2 S-, b is 1 to 4;
[0019] Y 1 , Y 2 , Y 3 , Y 4 Each independently represents -H;
[0020] R 2 and R 3 are each independently selected from a phenylene ring.
[0021] In an optional embodiment, the above-mentioned single ion conductor polymer can be prepared by the following steps: subjecting the raw material monomer to a thiol-ene click reaction under ultraviolet light irradiation to obtain the single ion conductor polymer. The wavelength of the ultraviolet light is preferably 365 nm.
[0022] Further, based on 1 mL of polar organic solvent, the single ion conductor polymer is 1 to 100 mg; preferably, based on 1 mL of polar organic solvent, the single ion conductor polymer is 5 to 20 mg.
[0023] Furthermore, the polar organic solvent is selected from one or a combination of two or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
[0024] The present invention also provides a coating, which is obtained by coating the above-mentioned coating.
[0025] Furthermore, the thickness of the coating is 10 to 5000 nm; preferably, the thickness of the coating is 50 to 1000 nm.
[0026] Furthermore, the coating amount is 0.01 to 100 mg / cm 2 , coating amount = coating mass ÷ coating area. The coating amount has a great influence on the performance of the final lithium-ion battery. A large coating amount will lead to increased battery polarization and internal resistance. A small coating amount will cause defects in the polymer protective layer and fail to ensure stable battery cycle performance. Preferably, the coating amount is 0.1-5 mg / cm 2 .
[0027] In a preferred embodiment, the coating is prepared by the following steps: applying the coating to the surface of the substrate, and then removing the polar organic solvent to obtain the coating. The coating method is blade coating or spin coating, and spin coating is more preferred.
[0028] The present invention also provides a lithium-ion battery, comprising a negative electrode sheet, a separator and a positive electrode sheet, wherein the negative electrode sheet comprises a negative electrode active material substrate and the aforementioned coating disposed thereon; or the negative electrode sheet comprises a current collector material substrate and the aforementioned coating disposed thereon.
[0029] Furthermore, the negative electrode active material is metallic lithium.
[0030] Furthermore, the current collector material is bare copper foil.
[0031] Compared with the prior art, the present invention achieves the following beneficial effects:
[0032] The lithium metal battery negative electrode single ion conductor polymer coating of the present invention can actively adjust the micro-sized solvation structure at the negative electrode interface. On the polymer skeleton, the high charge delocalization in the fixed and rigid sulfonyl imide anion increases the degree of freedom of the cation, creates loosely coordinated lithium ions, greatly reduces the local aggregation of free cations on the electrode surface, optimizes the lithium ion flux and inhibits the growth of lithium dendrites induced by space charge. At the same time, the flexible ether oxygen (sulfur) atoms and the released free lithium ions are strongly complexed with each other, and fast channels are constructed between the anion sites to assist their jumping within and between polymer chains, promoting the uniform nucleation of lithium at the interface and the lateral diffusion deposition of ion nanochannels along the interface.
[0033] The lithium metal battery negative electrode single ion conductor polymer coating of the present invention can participate in the construction of a stable SEI interface, reduce the consumption of active lithium required to form the SEI film and the consumption of solvent caused by side reactions, and promote the inorganic layer of the SEI to produce a low-impedance sulfide component.
[0034] The lithium ion battery negative electrode polymer protective coating of the present invention is simple to operate and takes a short preparation time, significantly reduces the amount of single ion conductor polymer solid material used and reduces the actual production cost, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The polymer single ion conductor in Example 1 of the present invention is shown 1 H NMR spectra;
[0036] Figure 2 The polymer single ion conductor in Example 1 of the present invention is shown 7 H NMR spectra;
[0037] Figure 3 shows an infrared image of the polymer single ion conductor in Example 1 of the present invention;
[0038] Figure 4 The thermogravimetric diagram of the polymer single ion conductor in Example 1 of the present invention is shown;
[0039] Figure 5 A cycle comparison diagram of the Li / NCM811 battery of Example 1 containing a coating and Comparative Example 1 without a coating at a rate of 0.5C is shown;
[0040] Figure 6 A cycle comparison diagram of the Cu / NCM811 battery of Example 2 containing a coating and Comparative Example 2 without a coating at a rate of 0.5C is shown;
[0041] Figure 7 The capacity density of Example 3 containing the coating layer in the nucleation stage is shown to be 0.1 mAh / cm 2 SEM image of lithium metal;
[0042] Figure 8 The capacity density of Example 4 containing the coating during the growth phase is shown to be 4 mAh / cm 2 SEM image of lithium metal;
[0043] Fig. 9 The capacity density of Comparative Example 3 without coating in the nucleation stage is 0.1 mAh / cm 2 SEM image of lithium metal;
[0044] Fig.10 The capacity density of Comparative Example 4 without coating during the growth phase is shown to be 4 mAh / cm 2 SEM image of lithium metal. DETAILED DESCRIPTION
[0045] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0046] Example 1
[0047] (I) This embodiment provides a single ion conductor polymer:
[0048]
[0049] Among them, the number average molecular weight is 12498g / mol, Z is N, R 1 -CH 2 CH 2 SCH 2 CH 2 OCH 2 CH 2 OCH 2 CH 2 SCH 2 CH 2 -, R 11 and R 12 The connecting groups are -CH 2 CH 2 -and-SCH 2 CH 2 -, X is O or S, Y 1 , Y 2 , Y 3 , Y 4 Both H, R 2 and R 3 is phenylene;
[0050] (II) This embodiment provides a method for preparing the above-mentioned single ion conductor polymer, and the reaction process is as follows:
[0051]
[0052] The preparation method specifically comprises the following steps: a solution containing 1.02 equivalents of 3,6-dioxa-1,8-octanedithiol is placed in a three-necked flask equipped with a magnetic stirrer, and then a solution containing 1.00 equivalents of lithium bis(4-phenylene)sulfonyl imide is added dropwise, and a thiol-ene click polymerization reaction is carried out at room temperature under an ultraviolet LED lamp for 48 hours. After the reaction is completed (by 1 HNMR monitoring), after removing N, N-dimethylformamide by extraction and separation, and drying in a vacuum oven at 100°C for 2 days, a white solid powder single ion conductor polymer (1.92 g) was obtained. The NMR results are as follows Figure 1 and Figure 2 As shown, the infrared results are Figure 3 The thermogravimetric analysis results are shown in Figure 4 shown.
[0053] (III) This embodiment provides a method for preparing a coating, which comprises the following steps:
[0054] A mixture of 50 mg of single ion conductor polymer and 5 ml of N-methylpyrrolidone was placed in a 20 ml transparent glass bottle and ultrasonicated for 30 minutes until the single ion conductor polymer was completely dissolved. Subsequently, the obtained viscous liquid was spin-coated on a copper foil at a speed of 3000 rpm using a spin coater for 30 seconds with a coating thickness of about 100 nm. After drying overnight at 100 ° C, the coated copper foil was cut into discs with a diameter of 14.0 mm and stored in a vacuum dryer at room temperature.
[0055] The coated copper foil (14 mm in diameter) was used as the negative electrode to assemble a lithium-copper half-cell and the 2 The current density of deposition was 4 mAh / cm 2 The lithium copper half-cell was then disassembled, and the coated copper foil with lithium metal deposited was taken out, and the copper foil with 4 mAh / cm 2 of lithium metal) as the negative electrode, and LiNi 0.8 Co 0.1 Mn 0.1 O 2(NCM811) was used as the positive electrode, aluminum foil was used as the positive electrode current collector, Celgard2325 was used as the separator, and 65 μL of electrolyte (formula: LiFSI:DME:HFE=1:2:2.2, molar ratio) was added. The button half-cell (CR2032) was assembled in the glove box and tested after standing for 24 hours. At room temperature of 25°C, the battery was activated by charging and discharging twice at a rate of 0.2C, and then long-cycle charging and discharging was performed at a rate of 0.5C, with a voltage range of 2.2V to 4.3V. The cycle results are shown in the figure. Figure 5 shown.
[0056] Example 2
[0057] (I) This embodiment provides a single ion conductor polymer:
[0058]
[0059] Among them, the number average molecular weight is 12498g / mol, Z is N, R 1 -CH 2 CH 2 SCH 2 CH 2 OCH 2 CH 2 OCH 2 CH 2 SCH 2 CH 2 -, R 11 and R 12 The connecting groups are -CH 2 CH 2 -and-SCH 2 CH 2 -, X is O or S, Y 1 , Y 2 , Y 3 , Y 4 Both H, R 2 and R 3 is phenylene;
[0060] (II) This embodiment provides a method for preparing the above-mentioned single ion conductor polymer, and the reaction process is as follows:
[0061]
[0062] The preparation method specifically comprises the following steps: a solution containing 1.02 equivalents of 3,6-dioxa-1,8-octanedithiol is placed in a three-necked flask equipped with a magnetic stirrer, and then a solution containing 1.00 equivalents of lithium bis(4-phenylene)sulfonyl imide is added dropwise, and a thiol-ene click polymerization reaction is carried out at room temperature under an ultraviolet LED lamp for 48 hours. After the reaction is completed (by 1 HNMR monitoring), and after removing N,N-dimethylformamide by extraction and separation, the mixture was dried in a vacuum oven at 100°C for 2 days to obtain a white solid powder single ion conductor polymer (1.92 g).
[0063] (III) This embodiment provides a method for preparing a coating, which comprises the following steps:
[0064] A mixture of 50 mg of single ion conductor polymer and 5 ml of N-methylpyrrolidone was placed in a 20 ml transparent glass bottle and ultrasonicated for 30 minutes until the single ion conductor polymer was completely dissolved. Subsequently, the obtained viscous liquid was spin-coated on the copper foil at a speed of 3000 rpm using a spin coater. The control time was 30 seconds, the coating thickness was about 100 nm, and the coating amount was 0.1 mg / cm 2 After drying at 100°C overnight, the coated copper foil was cut into discs with a diameter of 14.0 mm and stored in a vacuum dryer at room temperature.
[0065] The coated copper foil (14 mm in diameter) was used as the negative electrode, and LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) was used as the positive electrode, aluminum foil was used as the positive electrode current collector, Celgard2325 was used as the separator, and 65 μL of electrolyte (formula: LiFSI:DME:HFE=1:2:2.2, molar ratio) was added. The button half-cell (CR2032) was assembled in the glove box and tested after standing for 24 hours. At room temperature of 25°C, the battery was activated by charging and discharging twice at a rate of 0.2C, and then long-cycle charging and discharging was performed at a rate of 0.5C, with a voltage range of 2.2V to 4.3V. The cycle results are shown in the figure. Figure 6 shown.
[0066] Example 3
[0067] (I) This embodiment provides a single ion conductor polymer:
[0068]
[0069] Among them, the number average molecular weight is 12498g / mol, Z is N, R 1 -CH 2 CH2 SCH 2 CH 2 OCH 2 CH 2 OCH 2 CH 2 SCH 2 CH 2 -, R 11 and R 12 The connecting groups are -CH 2 CH 2 -and-SCH 2 CH 2 -, X is O or S, Y 1 , Y 2 , Y 3 , Y 4 Both H, R 2 and R 3 is phenylene;
[0070] (II) This embodiment provides a method for preparing the above-mentioned single ion conductor polymer, and the reaction process is as follows:
[0071]
[0072] The preparation method specifically comprises the following steps: a solution containing 1.02 equivalents of 3,6-dioxa-1,8-octanedithiol is placed in a three-necked flask equipped with a magnetic stirrer, and then a solution containing 1.00 equivalents of lithium bis(4-phenylene)sulfonyl imide is added dropwise, and a thiol-ene click polymerization reaction is carried out at room temperature under an ultraviolet LED lamp for 48 hours. After the reaction is completed (by 1 HNMR monitoring), and after removing N,N-dimethylformamide by extraction and separation, the mixture was dried in a vacuum oven at 100°C for 2 days to obtain a white solid powder single ion conductor polymer (1.92 g).
[0073] (III) This embodiment provides a method for preparing a coating, which comprises the following steps:
[0074] A mixture of 50 mg of single ion conductor polymer and 5 ml of N-methylpyrrolidone was placed in a 20 ml transparent glass bottle and ultrasonicated for 30 minutes until the single ion conductor polymer was completely dissolved. Subsequently, the obtained viscous liquid was spin-coated on the copper foil at a speed of 3000 rpm using a spin coater. The control time was 30 seconds, the coating thickness was about 100 nm, and the coating amount was 0.1 mg / cm 2 After drying at 100°C overnight, the coated copper foil was cut into discs with a diameter of 14.0 mm and stored in a vacuum dryer at room temperature.
[0075] The coated copper foil (14 mm in diameter) was used as the negative electrode to assemble a lithium-copper half-cell and the 2 The current density deposition capacity density is 0.1 mAh / cm 2 The lithium metal corresponds to the nucleation stage of lithium metal. The lithium copper half-cell was then disassembled in a glove box, and the copper foil with single ion conductor polymer coating on which lithium metal was deposited was taken out. It was washed with DME solvent and the excess solvent was naturally evaporated. It was then vacuum transferred to a scanning electron microscope for observation of its morphology. The scanning electron microscope characterization results are shown in the figure. Figure 7 shown.
[0076] Example 4
[0077] (I) This embodiment provides a single ion conductor polymer:
[0078]
[0079] Among them, the number average molecular weight is 12498g / mol, Z is N, R 1 -CH 2 CH 2 SCH 2 CH 2 OCH 2 CH 2 OCH 2 CH 2 SCH 2 CH 2 -, R 11 and R 12 The connecting groups are -CH 2 CH 2 -and-SCH 2 CH 2 -, X is O or S, Y 1 , Y 2 , Y 3 , Y 4 Both H, R 2 and R 3 is phenylene;
[0080] (II) This embodiment provides a method for preparing the above-mentioned single ion conductor polymer, and the reaction process is as follows:
[0081]
[0082] The preparation method specifically comprises the following steps: a solution containing 1.02 equivalents of 3,6-dioxa-1,8-octanedithiol is placed in a three-necked flask equipped with a magnetic stirrer, and then a solution containing 1.00 equivalents of lithium bis(4-phenylene)sulfonyl imide is added dropwise, and a thiol-ene click polymerization reaction is carried out at room temperature under an ultraviolet LED lamp for 48 hours. After the reaction is completed (by 1 HNMR monitoring), and after removing N,N-dimethylformamide by extraction and separation, the mixture was dried in a vacuum oven at 100°C for 2 days to obtain a white solid powder single ion conductor polymer (1.92 g).
[0083] (III) This embodiment provides a method for preparing a coating, which comprises the following steps:
[0084] A mixture of 50 mg of single ion conductor polymer and 5 ml of N-methylpyrrolidone was placed in a 20 ml transparent glass bottle and ultrasonicated for 30 minutes until the single ion conductor polymer was completely dissolved. Subsequently, the obtained viscous liquid was spin-coated on the copper foil at a speed of 3000 rpm using a spin coater. The control time was 30 seconds, the coating thickness was about 100 nm, and the coating amount was 0.1 mg / cm 2 After drying at 100°C overnight, the coated copper foil was cut into discs with a diameter of 14.0 mm and stored in a vacuum dryer at room temperature.
[0085] The coated copper foil (14 mm in diameter) was used as the negative electrode to assemble a lithium-copper half-cell and the 2 The current density deposition capacity density is 4 mAh / cm 2 The lithium metal corresponds to the growth stage of lithium metal. Then the lithium copper half-cell was disassembled in the glove box, and the copper foil with single ion conductor polymer coating on which lithium metal was deposited was taken out, washed with DME solvent and the excess solvent was naturally evaporated, and vacuum transferred into a scanning electron microscope to observe its morphology. The scanning electron microscope characterization results are shown in Figure 8 shown.
[0086] Example 5
[0087] (I) This embodiment provides a single ion conductor polymer:
[0088]
[0089] Where Z is N, R 1 For-SCH 2 CH 2 C(O)OCH 2 CH 2 (OCH 2 CH 2 ) m OCH2 CH 2 OC(O)CH 2 CH 2 S-, R 11 and R 12 The linking groups are -SCH 2 CH 2 C(O)-and-OC(O)CH 2 CH 2 S-, X is O, m is 4.22 to 4.23, Y 1 , Y 2 , Y 3 , Y 4 Both H, R 2 and R 3 is phenylene;
[0090] (II) This embodiment provides a method for preparing the above-mentioned single ion conductor polymer, and the reaction process is as follows:
[0091]
[0092] This embodiment provides a method for preparing a single ion conductor polymer, which is prepared by the following steps: 50 mL of N, N-dimethylformamide solution containing 4.68 g of lithium bis(4-mercaptophenyl)sulfonamide (12.75 mmol) is placed in a 150 mL three-necked flask equipped with a magnetic stirrer, and then N, N-dimethylformamide solution (50 mL) containing polyethylene glycol diacrylate (5 g, 12.5 mmol) is added dropwise, and a mercapto-ene click polymerization reaction is carried out at room temperature under an ultraviolet LED lamp (365 nm) for 48 hours. After the reaction is completed (by 1 HNMR monitoring), and after removing N,N-dimethylformamide by extraction and separation, the mixture was dried in a vacuum oven at 100°C for 2 days to obtain a white solid powder single ion conductor polymer (2 g).
[0093] (III) This embodiment provides a method for preparing a coating, which comprises the following steps:
[0094] A mixture of 50 mg of single ion conductor polymer and 5 ml of N-methylpyrrolidone was placed in a 20 ml transparent glass bottle and ultrasonicated for 30 minutes until the single ion conductor polymer was completely dissolved. Subsequently, the obtained viscous liquid was spin-coated on the copper foil at a speed of 3000 rpm using a spin coater. The control time was 30 seconds, the coating thickness was about 80 nm, and the coating amount was 0.1 mg / cm 2 After drying at 100°C overnight, the coated copper foil was cut into discs with a diameter of 14.0 mm and stored in a vacuum dryer at room temperature.
[0095] The coated copper foil (14 mm in diameter) was used as the negative electrode to assemble a lithium-copper half-cell and the 2 The current density of deposition was 4 mAh / cm 2 The lithium copper half-cell was then disassembled, and the copper foil with single ion conductor polymer coating on which lithium metal was deposited was taken out, and the copper foil with single ion conductor polymer coating on which lithium metal was deposited was taken out. 2 of lithium metal) as the negative electrode, and LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) is used as the positive electrode, aluminum foil is used as the positive electrode current collector, Celgard2325 is used as the separator, and 65μL of electrolyte (formula is LiFSI:DME:HFE=1:2:2.2, molar ratio) is added, and button half-cell (CR2032) is assembled in the glove box and tested after standing for 24 hours. At room temperature of 25℃, the battery is activated by charging and discharging twice at a rate of 0.2C, and then long-cycle charging and discharging is performed at a rate of 0.5C, with a voltage range of 2.2V to 4.3V.
[0096] Comparative Example 1
[0097] The difference between Comparative Example 1 and Example 1 is that the assembled lithium metal battery negative electrode does not have a single ion conductor polymer coating, and the rest of the processes are exactly the same.
[0098] A lithium-copper half-cell was assembled using ordinary copper foil (14 mm in diameter) as the negative electrode and charged at 0.5 mA / cm 2 The current density of deposition was 4 mAh / cm 2 The lithium copper half-cell was then disassembled, and the copper foil with lithium metal deposited was taken out, and the copper foil with lithium metal deposited was used as the lithium metal deposited. 2 of lithium metal) as the negative electrode, and LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) was used as the positive electrode, aluminum foil was used as the positive electrode current collector, Celgard2325 was used as the separator, and 65 μL of electrolyte (LiFSI:DME:HFE=1:2:2.2, molar ratio) was added. The button half-cell (CR2032) was assembled in the glove box and tested after standing for 24 hours. At room temperature of 25°C, the battery was activated by charging and discharging twice at a rate of 0.2C, and then long-cycle charging and discharging was performed at a rate of 0.5C, with a voltage range of 2.2V to 4.3V. The cycle results are shown in the figure. Figure 5 shown.
[0099] Comparative Example 2
[0100] The difference between Comparative Example 2 and Example 2 is that there is no single-ion conductor polymer coating on the surface of the copper current collector in the assembled negative electrode-free lithium metal battery, and the other processes are exactly the same.
[0101] Ordinary copper foil (14 mm in diameter) was used as the negative electrode, and LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811) was used as the positive electrode, aluminum foil was used as the positive electrode current collector, Celgard2325 was used as the separator, and 65 μL of electrolyte (LiFSI:DME:HFE=1:2:2.2, molar ratio) was added. The button half-cell (CR2032) was assembled in the glove box and tested after standing for 24 hours. At room temperature of 25°C, the battery was activated by charging and discharging twice at a rate of 0.2C, and then long-cycle charging and discharging was performed at a rate of 0.5C, with a voltage range of 2.2V to 4.3V. The cycle results are shown in the figure. Figure 6 shown.
[0102] Comparative Example 3
[0103] A lithium-copper half-cell was assembled using ordinary copper foil (14 mm in diameter) as the negative electrode and charged at 0.5 mA / cm 2 The current density of the deposition was 0.1 mAh / cm 2 The lithium metal was deposited in the glove box to study the morphology of the nucleation stage. The lithium copper half-cell was then disassembled in the glove box, and the copper foil with single ion conductor polymer coating on which lithium metal was deposited was taken out. The copper foil was washed with DME solvent and the excess solvent was naturally evaporated. The copper foil was vacuum transferred to a scanning electron microscope to observe its morphology. The scanning electron microscope characterization results are shown in the figure. Fig. 9 shown.
[0104] Comparative Example 4
[0105] A lithium-copper half-cell was assembled using ordinary copper foil (14 mm in diameter) as the negative electrode and charged at 0.5 mA / cm 2 The current density of deposition was 4 mAh / cm 2 The lithium metal was deposited in the glove box to study the morphology of the growth stage. The lithium copper half-cell was then disassembled in the glove box, and the copper foil with single ion conductor polymer coating on which lithium metal was deposited was taken out. It was washed with DME solvent and the excess solvent was naturally evaporated. It was then vacuum transferred to a scanning electron microscope to observe its morphology. The scanning electron microscope characterization results are shown in the figure. Fig.10 shown.
[0106] Figure 5 A cycle comparison diagram of the Li / NCM811 battery of Example 1 containing a coating and Comparative Example 1 without a coating at a rate of 0.5C is shown; Figure 6The figure shows the cycle comparison of the Cu / NCM811 battery of Example 2 with coating and Comparative Example 2 without coating at a rate of 0.5C. Figure 5 and Figure 6 It can be explained that compared with the comparative example 1 without coating, the embodiment 1 containing the single ion conductor coating shows better cycle stability, indicating that the single ion conductor coating effectively inhibits the side reaction at the negative electrode interface and reduces the loss of active lithium. After 200 cycles, the Li / NCM811 containing coating in embodiment 1 still maintains a discharge capacity of up to 88mAh / g, while the discharge capacity of the Li / NCM811 without coating in comparative example 1 has dropped to 30mAh / g and cannot maintain the cycle. In addition, the discharge capacity-time curve of the Cu / NCM811 battery under 0.5C conditions also proves that the coating-containing embodiment 2 has a higher capacity retention rate and a higher discharge capacity than comparative example 2.
[0107] Figure 7 The capacity density of Example 3 containing the coating layer in the nucleation stage is shown to be 0.1 mAh / cm 2 SEM image of lithium metal; Fig. 9 The capacity density of Comparative Example 3 without coating in the nucleation stage is 0.1 mAh / cm 2 SEM image of lithium metal. By comparing the SEM morphology images of the nucleation stage in Example 3 and Comparative Example 3, it can be found that in Comparative Example 3, lithium deposits of different shapes and sizes are generated on the uneven copper foil surface, while on the copper foil surface containing the polymer single ion conductor coating, more uniform and dense nuclei are generated, indicating that the uniformly distributed anion sites on the polymer single ion conductor coating effectively regulate the deposition behavior of lithium metal at the negative electrode interface by homogenizing the lithium ion flux.
[0108] Figure 8 The capacity density of Example 4 containing the coating during the growth phase is shown to be 4 mAh / cm 2 SEM image of lithium metal; Fig.10 The capacity density of Comparative Example 4 without coating during the growth phase is shown to be 4 mAh / cm 2 SEM image of lithium metal. Figure 8 and Fig.10 It can be found that the polymer single-ion coating significantly improves the deposition morphology of lithium metal, generating larger block-shaped deposits that are denser and more uniform; on the contrary, the lithium deposits without coating in the control example are smaller in size, have larger pores, and have unstable lithium dendrites.
Claims
1. A coating, wherein The coating comprises a single ion conductor polymer having a structure shown in formula (I) and a polar organic solvent; In the formula (I), n is 5 to 1000; Z means N, B or P; R1 means wherein m is 2 to 100; X represents a Group VIA element; Y1, Y2, Y3, and Y4 each independently represent H or a halogen; R 11 and R 12 Each independently represents a substituted or unsubstituted C1-C10 alkylene group, and the substitution position is a carbon atom and / or a hydrogen atom on the C1-C10 alkylene group; when the substitution position is a carbon atom on the C1-C10 alkylene group, the substituent is -O- or -S-; when the substitution position is a hydrogen atom on the C1-C10 alkylene group, the substituent is -F, -CH3 or =O; R2 and R3 are each independently selected from one or a combination of two or more of a F-substituted or unsubstituted C1-C4 alkylene ring, a phenylene ring, a naphthalene ring or a heterocyclic ring, wherein the heteroatom in the heterocyclic ring is selected from N, O or S.
2. The coating according to claim 1, wherein In the formula (I), The n is 20 to 200; The R1 is wherein m is 2 to 50; X is selected from O and / or S; Y1, Y2, Y3, and Y4 each independently represent H or F; R 11 Selected from -(CH2) a -、-(CF2) a -、-(CHF) a -, -CH2CH(CH3)C(O)-, -CH2CH2C(O)-, -S(CH2) a -、-S(CF2) a -、-S(CHF) a -, -SCH2CH(CH3)C(O)-, -SCH2CH2C(O)-, -O(CH2) a -、-O(CF2) a -、-O(CHF) a - and -OCH2CH(CH3)C(O)-, a is 1 to 10; the R 12 Selected from -(CH2) b -、-(CF2) b -、-(CHF) b -, -OC(O)CH2CH(CH3)-, -OC(O)CH2CH2-, -S(CH2) b -、-(CF2) b S-、-(CHF) b S-, -OC(O)CH(CH3)CH2S-, -OC(O)CH2CH2S-, -(CH2) b O-, -(CF2) b O-、-(CHF) b O- and -OCH2CH(CH3)C(O)O-, or a combination of two or more thereof, and b is 1 to 10; The R2 and R3 are each independently selected from one or a combination of two or more of F-substituted or unsubstituted C1-C4 alkylene, a phenylene ring, a naphthalene ring, a sub-five-membered heterocycle or a sub-six-membered heterocycle, and the heteroatoms in the sub-five-membered heterocycle and the sub-six-membered heterocycle are each independently selected from N, O or S.
3. The coating according to claim 1, wherein The number average molecular weight of the single ion conductor polymer is 10000 to 20000 g / mol; Said Z represents N; The R1 is wherein m is 2 to 7; X represents O and / or S; R 11 Selected from -(CH2) a -, -SCH2CH2C(O)-, wherein a is 1 to 4; wherein R 12 Selected from -S(CH2) b -, -OC(O)CH2CH2S-, wherein b is 1 to 4; The Y1, the Y2, the Y3, and the Y4 each independently represent -H; The R2 and R3 are each independently selected from a phenylene ring.
4. The coating according to claim 1, wherein The single ion conductor polymer is obtained by subjecting raw material monomers to a mercapto-ene click reaction under ultraviolet light irradiation.
5. The coating according to claim 1, wherein The single ion conductor polymer is 1 to 100 mg based on 1 mL of the polar organic solvent; Preferably, based on 1 mL of the polar organic solvent, the single ion conductor polymer is 5 to 20 mg.
6. The coating according to claim 1, wherein The polar organic solvent is selected from one or a combination of two or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
7. A coating, wherein The coating is obtained by coating the coating material according to any one of claims 1 to 6.
8. The coating according to claim 7, wherein The thickness of the coating is 10 to 5000 nm; Preferably, the coating has a thickness of 50 to 1000 nm.
9. The coating according to claim 7, wherein The coating amount is 0.01-100 mg / cm 2 ; Preferably, the coating amount is 0.1-5 mg / cm 2 .
10. A lithium ion battery comprising a negative electrode sheet, a separator and a positive electrode sheet, wherein: The negative electrode sheet comprises a negative electrode active material substrate and a coating as claimed in any one of claims 7 to 9 disposed thereon; or The negative electrode sheet comprises a current collector material substrate and a coating according to any one of claims 7 to 9 disposed thereon.
Citation Information
Patent Citations
Lithium metal anode protective layer and preparation method and application thereof
CN111435728A
Lithium ion secondary battery and electrolyte thereof
CN103199302A
Preparation method of single-ion conductive polymer composite material for lithium metal secondary battery
CN112421046A
Boron-rich single-ion polymer artificial SEI (solid electrolyte interface) membrane as well as preparation method and application thereof
CN115692710A
Lithium ion conductive organic-inorganic composite separator and lithium secondary battery comprising the same
KR1020170032002A